ALOINJERTO DE MATRIZ DÉRMICA ACELULAR COMO SUSTITUTO DE TEJIDO DADOR PALATINO. - Sueldo Rivero, Efraín (1998)
Soft-tissue augmentation procedures to increase the existing or create a new Zone of attached keratinized gingival tissue have been routinely performed using the patient's masticatory mucosa as the donor material. Predictable tissue regeneration presents a considerable challenge in surgical treatment of tissue defects. AlloDerm (R) represent a significant advancement and augmentation.